Engineering plastics handbook - Margolis, James M. (McGraw-Hill's AccessEngineering., 2006)
Product developers have found a wide array of application for thermoplastics in automotive interior and exterior parts, business machines, medical, telecommunications equipment, microwaveable packaging, appliances, and specialty uses. However, finding a material that can meet consumer demands is no small task. While technological information is readily available regarding the general properties of common thermoplastic materials, there is no single authoritative source for building and evaluating new product lines. Written by a top team of international experts, this book focuses only on new and emerging engineering resin property requirements, instead of on properties of conventional engineering thermoplastics available from polymer producers and compounders. The book covers the important chemical, physical, mechanical, and applications aspects of engineering thermoplastics in one place, providing clear solutions to evaluate and compare existing product lines and new and emerging products.